Factors impacting the antioxidant/prooxidant activity of tea polyphenols on lipids and proteins in oil-in-water emulsions. (15th February 2022) - Tian, Li; Zhang, Shulin; Yi, Jianhua; Zhu, Zhenbao; Cui, Leqi; Decker, Eric Andrew; McClements, David Julian
Abstract: Tea polyphenols (TP) may inhibit or promote the oxidation of proteins and lipids in foods, depending on system conditions. In this study, we examined the effects of TP concentration (0, 100, and 400 mg/L), solution pH (3 and 7), and the addition of ethylenediaminetetraacetic acid (0 or 20 μmol/L EDTA) on the antioxidant/prooxidant activities of TP in walnut oil-in-water (O/W) emulsions under accelerated storage conditions (50 °C for 0, 48, 96 h). At pH 3, a lower concentration of TP (100 mg/L) exhibited stronger antioxidant activity for lipids and proteins than the higher concentration (400 mg/L). At pH 7, the lower concentration of polyphenols was still more effective, while the higher concentration resulted in prooxidant activity toward the proteins. In the absence of TP, the incorporation of EDTA into the emulsions (pH 7) inhibited lipid and protein oxidation, which was attributed to its ability to chelate and inactivate the prooxidant transition metals. Interestingly, the antioxidant activity of EDTA decreased in the presence of TP. Therefore, these results suggested that TP could be used to retard protein and lipid oxidation in emulsion-based foods, but their levels should be optimized due to their complex prooxidant and antioxidant mechanisms, depending on system composition and environmental conditions. Highlights: Tea polyphenols acted as antioxidants toward lipids and proteins at pH 3. The pro/antioxidant activity of tea polyphenols for proteins depended on dose at pH 7. EDTA addition improved the oxidative stability of emulsions at pH 7 and pH 3. Tea polyphenols reduced the antioxidant potency of EDTA.